Variability in correction and speech therapy work with the children of primary school age with ASD and intellectual disability - Andreeva S.V (Moscow State University of Psychology and Education, 2017)
Speech disorders in children with autism spectrum disorders are variable and polymorphic, which creates the need for variability in correctional approaches in speech therapy. Present article shows the techniques which are used in practice of language correction therapy, especially in correction of speech underdevelopment at the stage of the formation of phrasal speech in children with ASD in conjecture with intellectual disability. The importance of social development of children, perceptivity in the formation of higher mental functions, in particular, speech and thinking, is stressed.